Improving the quality of discharge care plan in the heart failure with reduced ejection fraction (HFrEF) cohort: a quality improvement study. (14th October 2021) - Hey, C; Zahoor, S; Shreeve, J; Gomes, L; Varghese, S; Alam, T; Zaman, J; Nair, S
Abstract: Background: High-quality heart failure (HF) discharge summary (DS) is the cornerstone of effective communication during the transition from specialists to primary care. The combination of continuing involvement of multidisciplinary members, varying individual tolerance to treatments, and the need for multiple investigations beget intricate HFrEF management. The quality of the information included in DS following HF-related hospitalisation varies widely and may be sub-optimal in communicating patient's in-hospital care, leading to inadequate compliance to guideline-directed medical therapy (GDMT) and increased risk of re-hospitalisation. Notwithstanding this real-world observation, there remains a paucity of consensus on the standard of measurements of HF DS. Purpose: We aimed to optimise the transmission of information between patients and HF multidisciplinary members to improve adherence to GDMT, follow-up (F/U) care coordination and patient education in line with the National Institute for Health and Care Excellence (NICE) and the European Society of Cardiology (ESC) recommendations. Methods: A random sampling of the HFrEF cohort discharged from the cardiac unit at our institution following HF-related hospitalisation was performed across four distinct time points matched with respective interventions. Three iterative cycles (baseline analysis and two educational interventions – departmental teaching and dissemination of innovative mnemonics sheets – THE WET TO DRY [Figure 1]) were completed using Plan-Do-Study-Act (PDSA) methodology. The quality of patients DS was objectively analysed based on the inclusion of physiological and investigation parameters, in-patient treatment, initiation/titration of GDMT, F/U care coordination, and patient education. Results: Sixty-six patients, mean±SD age 74.6±12.8y were enrolled between 2018–2021. The baseline reporting of presenting complaints, trigger and investigation findings were high and consistent throughout all cycles. A positive trend was observed in the reporting of physiological parameters and in-patient treatment post-interventions. Patient education and vaccines offered remained low despite improving compliance. As such, a consensus on the provision of nurse-led pre-discharge review label and interactive patient personal passport (Figure 1) was achieved via a group of cardiologists and HF specialist nurses to address identified practice gap from preceding PDSA cycles. Full adherence to GDMT and the inclusion of F/U pathway were observed following the provision of nurse-led review label (Figure 2). Conclusion: This study demonstrates that educational interventions – departmental teaching and innovative mnemonics can be effective in improving the quality of HF DS. Structured nurse-led review label and interactive patient personal passport are feasible interventions, which can be implemented at minimal cost to sustain adherence to GDMT, F/U care coordination and individualised patient education. Funding Acknowledgement: Type of funding sources: None.